2014
DOI: 10.1186/1472-6831-14-135
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess oral health literacy by comparing a word recognition and comprehension tool

Abstract: BackgroundOral health literacy is important to oral health outcomes. Very little has been established on comparing word recognition to comprehension in oral health literacy especially in older adults. Our goal was to compare methods to measure oral health literacy in older adults by using the Rapid Estimate of Literacy in Dentistry (REALD-30) tool including word recognition and comprehension and by assessing comprehension of a brochure about dry mouth.Methods75 males and 75 females were recruited from the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
3
22
2
Order By: Relevance
“…This confirms the association between word recognition and comprehension for this measure. Noting that the mean for the REALMD‐20 (17.2 of 20 items) was higher than for the CMOHK (17.6 of 23 items) also confirms the results of Khan et al., who showed that word pronunciation and knowledge were not the same, and that, in more cases, recognition was more common than knowledge . In Khan's case, participants’ use of knowledge was represented by a simple definition.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This confirms the association between word recognition and comprehension for this measure. Noting that the mean for the REALMD‐20 (17.2 of 20 items) was higher than for the CMOHK (17.6 of 23 items) also confirms the results of Khan et al., who showed that word pronunciation and knowledge were not the same, and that, in more cases, recognition was more common than knowledge . In Khan's case, participants’ use of knowledge was represented by a simple definition.…”
Section: Discussionsupporting
confidence: 77%
“…People have questioned whether recognition of a word indicates that the individual comprehends the meaning . This analysis demonstrates for oral HL that words that dentists use may be recognized but not completely understood by their patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations